Mycorrhizas influence functional traits of two tallgrass prairie species - Weremijewicz, Joanna (Ecol Evol, 2016)
Over the past decade, functional traits that influence plant performance and thus, population, community, and ecosystem biology have garnered increasing attention. Generally lacking, however, has been consideration of how ubiquitous arbuscular mycorrhizas influence plant allometric and stoichiometric functional traits. We assessed how plant dependence on and responsiveness to mycorrhizas influence plant functional traits of a warm‐season, C4 grass, Andropogon gerardii Vitman, and the contrasting, cool‐season, C3 grass, Elymus canadensis L. We grew both host species with and without inoculation with mycorrhizal fungi, across a broad gradient of soil phosphorus availabilities. Both host species were facultatively mycotrophic, able to grow without mycorrhizas at high soil phosphorus availability. A. gerardii was most dependent upon mycorrhizas and E. canadensis was weakly dependent, but highly responsive to mycorrhizas. The high dependence of A. gerardii on mycorrhizas resulted in higher tissue P and N concentrations of inoculated than noninoculated plants. When not inoculated, E. canadensis was able to take up both P and N in similar amounts to inoculated plants because of its weak dependence on mycorrhizas for nutrient uptake and its pronounced ability to change root‐to‐shoot ratios. Unlike other highly dependent species, A. gerardii had a high root‐to‐shoot ratio and was able to suppress colonization by mycorrhizal fungi at high soil fertilities. E. canadensis, however, was unable to suppress colonization and had a lower root‐to shoot ratio than A. gerardii. The mycorrhiza‐related functional traits of both host species likely influence their performance in nature: both species attained the maximum responsiveness from mycorrhizas at soil phosphorus availabilities similar to those of tallgrass prairies. Dependence upon mycorrhizas affects performance in the absence of mycorrhizas. Responsiveness to mycorrhizal fungi is also a function of the environment and can be influenced by both mycorrhizal fungus species and soil fertility.